Diabetes Mellitus and Chronic Obstructive Pulmonary Disease: An Overview - Katsiki, Niki; Steiropoulos, Paschalis; Papanas, Nikolaos; Mikhailidis, Dimitri P. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Chronic obstructive pulmonary disease (COPD) is a common disease with an increasing prevalence, characterised by persistent respiratory symptoms and airflow limitation. Apart from cigarette smoking, certain occupational and environmental exposures, low socioeconomic status and genetic factors may contribute to the pathogenesis of COPD. Comorbidities, e. g. diabetes mellitus (DM), can negatively affect quality of life, COPD outcomes and cardiovascular risk. The present narrative review considers the potential links between COPD and DM, such as systemic inflammation, oxidative stress, hypoxaemia and hyperglycaemia. The effects of antidiabetic drugs on lung function and COPD outcomes, as well as the possibility of common therapeutic modalities are also briefly considered. Further research is needed in this field to elucidate these relationships as well as their potential clinical implications in daily practice.
Keywords: chronic obstructive pulmonary disease; obesity; type 2 diabetes mellitus